Pentingnya Pendidikan Nilai Moral Bagi Generasi Penerus - Ahmad Nawawi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Moral/ Religion Values Education in Indonesia from 1968 to now a days are still neglected, it has not been addressed in a planned and serious. This is proved by the number of hours learning that has nuances of religious and moral education in minimal, it is only 2 to 4 hours per week than the hours from 34 to 42 hours per week. Whereas by KTSP, it is actually more manageable, so that these needs can be accommodated and fulfilled. Moral/ Religion Values Education is very important for youth as the future generation, that lifted the nation’s dignity, increasing quality of life, life for the better, safe and comfortable and prosperous. Education is to form the next generation who has German brains and has Mecca heart that reflects a balance between knowledge and practice of the moral / religious values. Ideal conditions of the next generation youth, as an individual who is growing, and therefore need to be given the opportunity to grow in proportion, directed, and optimal and get a balanced education services between knowledge and moral / religion education. They have a role and position strategic in the continuity of the nation life. But the factual conditions in the field as it appears in print and electronic media, in fact as the next generation, youths caught up in immoral behavior that is very worrying and fearing even disturbing the public, such as the emergence of biker gangs, fights (students, university students, and even between villages involving mass ). It is predicted as a result of the neglect of Moral Values Education in Indonesia. Therefore, this writing tries to explore based on literature review and the real conditions in the field to obtain a reliable solution / cespleng. Assisted by the Social and Moral Development theories of Albert Bandura and Kohlberg expected a solution to encourage the implementation of Moral/ Religion Values Education in Indonesia. Keywords: Moral Values Education / Religion, next generation.